2014
DOI: 10.1155/2014/842569
|View full text |Cite
|
Sign up to set email alerts
|

[6]-Shogaol Inhibitsα-MSH-Induced Melanogenesis through the Acceleration of ERK and PI3K/Akt-Mediated MITF Degradation

Abstract: [6]-Shogaol is the main biologically active component of ginger. Previous reports showed that [6]-shogaol has several pharmacological characteristics, such as antioxidative, anti-inflammatory, antimicrobial, and anticarcinogenic properties. However, the effects of [6]-shogaol on melanogenesis remain to be elucidated. The study aimed to evaluate the potential skin whitening mechanisms of [6]-shogaol. The effects of [6]-shogaol on cell viability, melanin content, tyrosinase activity, and the expression of the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 31 publications
3
37
0
1
Order By: Relevance
“…It was suggested that a decrease in the protein expression levels of TRP‐1 and MITF by bioactive compound known as [6]‐shogaol (C 17 H 24 O 3 ) and Gomisin N (C 23 H 28 O 6 ) was due to the degradation of MITF protein via acceleration of ERK and phosphatidylinositol‐3‐kinase (PI3K/Akt) pathway . It was also suggested that partially purified Nardostachys chinensis and 1‐O‐methyl‐fructofuranose (C 7 H 14 O 6 ) of Schisandra chinensis markedly reduced MITF, TRP1, TRP2, and TYR protein expressions via reduction of intracellular cAMP levels, and activation of MAPK/ERK and (PI3K)/Akt expression …”
Section: Depigmenting Compounds and Their Modulation On Melanogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that a decrease in the protein expression levels of TRP‐1 and MITF by bioactive compound known as [6]‐shogaol (C 17 H 24 O 3 ) and Gomisin N (C 23 H 28 O 6 ) was due to the degradation of MITF protein via acceleration of ERK and phosphatidylinositol‐3‐kinase (PI3K/Akt) pathway . It was also suggested that partially purified Nardostachys chinensis and 1‐O‐methyl‐fructofuranose (C 7 H 14 O 6 ) of Schisandra chinensis markedly reduced MITF, TRP1, TRP2, and TYR protein expressions via reduction of intracellular cAMP levels, and activation of MAPK/ERK and (PI3K)/Akt expression …”
Section: Depigmenting Compounds and Their Modulation On Melanogenesismentioning
confidence: 99%
“…Cells have been subjected to stimulants to mimic the actual condition of hyperpigmentation. Various stimulants such as radicals, UVB, α‐MSH, and SCF have been reported where the optimal conditions such as dose concentration, duration, and intensity are varied depending on experimental requirement . For instance, UVB at ~10‐30 mJ UVB, α‐MSH at ~10‐100 nmol/L, lipopolysaccharide (LPS) at 1 μg/mL, and SCF at ~100‐200 ng/mL were used in experiments .…”
Section: Protocol and Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, MITF directly binds to the promoter regions of melanin production genes which were the most important transcription factor involved in regulation of TYR gene expression . Tyrosinase plays an important role in regulating melanin production by the hydroxylation of tyrosine into dihydroxyphenylalanine (DOPA) followed by further oxidation of DOPA into DOPA quinone, finally resulting in the abnormal accumulation of melanin pigments . For these reasons, melanogenesis‐inhibitors could suppress the expressions of MITF and tyrosinase reasulting in decreasing melanin production.…”
Section: Introductionmentioning
confidence: 99%
“…이러한 생강의 효능을 나타내는 주 요 성분은 gingerols, shogaols, paradols 등이고, 이 중 신선한 생 강에 가장 많이 함유되어 있는 gingerols의 가수분해 산물이 바로 shogaols이다 (Bak et al, 2012;Huang et al, 2014) NFΚB reporter NIH3T3 stable cell line (2×10 ⁵ cells/well) was seeded on 60 mm culture dish and then incubated for 24 h. The cells were pre-treated with various concentrations of 6-shogaol for 6 h. Then, the cells were washed by PBS and irradiated by 10 J/cm² UVA. After further incubation for 24 h, inhibition of NFΚB promoter activity by 6-shogaol was determined by the NFΚB promoter luciferase assay.…”
mentioning
confidence: 99%